Novejše norme MOD in koncept dostojnega dela - Tičar, Luka (Delavci in delodajalci, 2015)
In his paper the author draws attention to the concept of decent work as a fundamental value of the normative and other activities of the ILO in the past twenty years. A short introductory outline of the contents of this concept is followed by an in-depth analysis of the two binding international documents in the field of decent work: the ILO convention no. 189 on decent work of domestic workers and the Protocol to ILO Convention no. 29 on forced labour, the former adopted in 2011, the latter in 2014. The author also discusses recommendations (no. 201 and 203) attached to the two binding documents. All four international documents are discussed within the context of Slovenian labour law system.
Keywords: delo; delo na črno; trg dela; varnost pri delu; varstvo pri delu; zaposlovanje